LEGAL POLITICS DESA ADAT DALAM MENGATUR KRAMA TAMIU (Studi Kasus di Desa Bayad, Kecamatan Tegalalang, Kabupaten Gianyar) - I Putu Sastra Wibawa (Jurnal PASUPATI, 2013)
Abstract Pakraman Village courage and competent in organizing migrants / Krama Tamiu will surely come from the authority of the traditional village autonomy, also sourced from politics and made laws outlined by the provincial government of Bali itself. Krama Tamiu legal political arrangement certainly has a strategic rationale, one which is not just local government is involved in regulating Krama Tamiu , but also involve the participation of traditional village in implementation.However, often times the legal implementation encountered some obstacles and problems, both technical and non-technical issues, such as the one that occurred in the village of Bayad . Thus the researchers wanted to examine and study more about the "Legal Politics traditional village In regulate Krama Tamiu (Case Study on the village of Bayad, District Ubud, Gianyar regency)".        Issues discussed include (1) Why Krama Tamiu settings need to be done in Bayad Pakraman Village? (2). How Krama Tamiu regulatory mechanisms in Bayad Pakraman Village? and (3) What are the implications and barriers to the implementation of the rules on Krama Tamiu in Bayad Pakraman Village?. Types of research that are used in discussing these issues is qualitative. Keywords : Legal Politics, Krama Tamiu.